2006
DOI: 10.1074/jbc.m512375200
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Activation of Oncoprotein Kinase Tpl2/Cot in HTLV-I-transformed T Cells

Abstract: Protein kinase Tpl2/Cot is encoded by a protooncogene that is cis-activated by retroviral insertion in murine T cell lymphomas. It has remained unclear whether this oncoprotein kinase is mutated or post-translationally activated in human cancer cells. We have shown here that Tpl2/Cot is constitutively activated in human leukemia cell lines transformed by the human T cell leukemia virus type I (HTLV-I). The kinase activity of Tpl2/Cot is normally suppressed through its physical interaction with an inhibitor, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Also, Cot kinase was found to be constitutively activated in several human T cell leukemia cell lines [42], and BCL11B was recently identified as a potential oncogene for ATL [43]. Thus, our data may also suggest an interesting functional link between enhanced expression of BCL11B and the NF-kB constitutive activation in the adult T cell leukemia/lymphoma cells.…”
Section: Discussionsupporting
confidence: 54%
“…Also, Cot kinase was found to be constitutively activated in several human T cell leukemia cell lines [42], and BCL11B was recently identified as a potential oncogene for ATL [43]. Thus, our data may also suggest an interesting functional link between enhanced expression of BCL11B and the NF-kB constitutive activation in the adult T cell leukemia/lymphoma cells.…”
Section: Discussionsupporting
confidence: 54%
“…IL-2 induction by TPL-2 has also been suggested to involve activation of NF-κB transcription factors via the related MAP3 kinase NIK [23,24]. Transfection experiments in Jurkat T cells indicate that TPL-2 may control NF-κB activity by modulating the transactivation potential of the RelA transcription factor [25,26]. In addition, overexpression experiments in COS-7 cells demonstrate that TPL-2, which is complexed with the NF-κB inhibitory protein NF-κB1 p105 [27] (see section 3), may regulate NF-κB activation by inducing p105 proteolysis, releasing associated Rel subunits for translocation into the nucleus [28].…”
Section: S125mentioning
confidence: 98%
“…Activated MAP3K8 induces the ERK1/2, JNK, NF-B, and p38MAPK pathways, and a study has shown that it is constitutively activated in HTLV-Itransformed human CD4ϩ T-cell lines. 59 The MAP3K8 gene therefore illustrates a gene deregulation (increased expression) detected in our patient cohort during chronic disease, which was further augmented in L-HES-associated T lymphoma and identified as a potential target of microRNAs shown to be downmodulated in the patients' cells.…”
Section: Discussionmentioning
confidence: 99%